2012
DOI: 10.1210/jc.2012-1996
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA Profiles in Patients with Metabolic Syndrome

Abstract: Significant dysregulation of seven candidate microRNAs has been found to be associated with risks involved in the manifestation of metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
294
3
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(329 citation statements)
references
References 20 publications
15
294
3
5
Order By: Relevance
“…Table 1). [13] Whilst a cluster of three microRNAs (miR-92a, miR-130a and miR-195) were reported to be uniquely dysregulated in hypertension and metabolic syndrome but not type 2 diabetes mellitus (T2DM) or hypercholesterolaemia, the study highlights the significant interplay in the pathology of these conditions. Whilst this makes identifying microRNAs that are dysregulated specifically in hypertension challenging, it raises the potential for microRNA-based therapeutics to target multiple cardiovascular pathologies.…”
Section: Circulating Micrornas and Novel Mechanisms Of Blood Pressurementioning
confidence: 88%
See 1 more Smart Citation
“…Table 1). [13] Whilst a cluster of three microRNAs (miR-92a, miR-130a and miR-195) were reported to be uniquely dysregulated in hypertension and metabolic syndrome but not type 2 diabetes mellitus (T2DM) or hypercholesterolaemia, the study highlights the significant interplay in the pathology of these conditions. Whilst this makes identifying microRNAs that are dysregulated specifically in hypertension challenging, it raises the potential for microRNA-based therapeutics to target multiple cardiovascular pathologies.…”
Section: Circulating Micrornas and Novel Mechanisms Of Blood Pressurementioning
confidence: 88%
“…Whilst this makes identifying microRNAs that are dysregulated specifically in hypertension challenging, it raises the potential for microRNA-based therapeutics to target multiple cardiovascular pathologies. It is also noteworthy that miR-92a was found to be present (and differentially expressed) in exosomes (isolated from serum), [13] which have been postulated to play a key role in facilitating microRNA-mediated cell-to-cell communication. [14,15] Pertinently, miR-92a was predicted to target AGTR1, the gene encoding the angiotensin II type I receptor (AT1R) -a key component of the renin-angiotensin system.…”
Section: Circulating Micrornas and Novel Mechanisms Of Blood Pressurementioning
confidence: 99%
“…For example, cholesterol is regulated at the cellular level by both classical transcription factors and also by miRNAs. With regard to their relevance as blood-based biomarkers for MetS, Karolina et al [21] investigated both total miRNAs isolated from whole blood and EV-contained miRNAs isolated from plasma of individuals with MetS, T2DM, hypercholesterolaemia (HCL), hypertension (HPT), and healthy controls (Table 3). Five miRNAs were identified as present in EVs from all groups.…”
Section: Studies Of Circulating Evs As Biomarkers For Mets Are Still mentioning
confidence: 99%
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
“…It is possible to extract all the miRNAs in the sample or to specifically extract miRNAs associated with particular vesicles or proteins. The large majority of the studies extract all the miRNAs, whereas some investigate only those associated with exosomes [20,34,65]. However, the profile of extracellular miRNAs associated with vesicles is different from that of vesicle-free miRNAs [13].…”
Section: Current Limits To the Use Of Circulating Mirnas In Clinical mentioning
confidence: 99%